Corporate debt and unconventional monetary policy: The risk-taking channel with bond and loan contracts - Takaoka, Sumiko; Takahashi, Koji (Journal of Financial Stability, 2022)
We investigate the effects of unconventional monetary policies on corporate debt through the risk-taking channel using corporate bond and syndicated loan contracts from 2000 to 2016 in Japan. In this period, the policy rate remained fixed near the zero bound. Using the daily changes in the yield curve on monetary policy meeting days, we identify one call rate shock and two unconventional monetary policy shocks that do not affect short-term rates. We find that QE shocks, which move all medium-to-long-term rates, increase the maturity of debt contracts, especially for syndicated loans. In addition, such QE shocks decrease the size of corporate bonds with short maturity. On the other hand, QQE shocks, which raise medium-term rates and lower long-term rates, decrease the size of loans and corporate bonds with longer maturity. These effects imply the existence of the risk-taking channel of unconventional monetary policy: it stimulates investment in longer-maturity assets and decreases investment in assets with lower yields. Our findings show that unconventional policies affect debt contracts even in an extremely low interest rate environment.